Quizwhizzer Learning Media Training On Interest In Learning Mathematics In Elementary School Students - Ana Uzla BatuBara; Bambang Suryanto; Ulfa Hanim (International Journal of Community Service Implementation, 2024)
Mathematics is an issue that we cannot separate from daily life. The characteristics of elementary school mathematics learning aim to develop students' logical, analytical, systematic, critical, and creative thinking abilities, as well as to foster a habit of working together in solving problems. Mathematics learning should be meaningful, emphasizing understanding of the material and its application rather than rote memorization. In meaningful learning, students learn mathematics starting from the process of forming a concept and then trying to apply and manipulate these concepts in new problems. Many students do not like mathematics. They consider mathematics to be the most difficult subject, leading to a sense of difficulty even before the lesson begins. Therefore, it is necessary to implement learning methods that motivate students to improve their academic performance. To assist students in enhancing their mathematics learning, educational media can be utilized, one of which is the Quiz whizzer Learning Media. Learning media serve to convey messages and can stimulate students' thoughts, feelings, and motivation, thereby encouraging the learning process. Media can take the form of teaching aids and tools. One of the e-learning media that can be used is the Quiz whizzer application.